Investigations of magnetic and dielectric properties of cupric oxide nanoparticles - Bhalerao-Panajkar, Rohini S.; Shirolkar, Mandar M.; Das, Raja; Maity, Tuhin; Poddar, Pankaj; Kulkarni, S. K. (Solid State Communications, 2011)
Cupric oxide nanoparticles of similar to 8-10 nm width and 40-45 nm length self assembled as large particles similar to 1-1 5 mu m have been investigated in the 10-325 K temperature range using magnetic and dielectric measurements In magnetic measurements a single broad peak at similar to 230 K in a zero field cooled sample has been observed Coercivity in magnetization measurements at 10 K suggests that the nanoparticles are core-shell type particles with an antiferromagnetic core and a ferromagnetic shell Dielectric measurements at various frequencies from 3 7 Hz to 949 kHz exhibit a sharp peak at 284 K followed by weak anomalies around 213 and 230 K (C) 2010 Elsevier Ltd All rights reserved
Keywords: CuO nanoparticles; Dielectric; Ferroelectric transition; Ferromagnetic

Ferromagnetic tetranuclear Cu(II) complex: catecholase and phenoxazinone synthase activities - Mitra, Merry; Kundu, Tanay; Kaur, Gurpreet; Sharma, Gyaneswar; Choudhury, Angshuman Roy; Singh, Yogesh; Ghosh, Rajarshi (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: catalysis; Ferromagnetic; Tetranuclear copper

Preparation and characterization of flexible ferromagnetic nanocomposites for microwave applications - Thomas, Teena; Kanoth, Bipinbal P.; Nijas, C. M.; Joy, Pattayil Alias; Joseph, Joseph M.; Kuthirummal, Narayanan; Thachil, Eby T. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2015)
Magnetic Fe3O4 nanoparticles (similar to 20 nm) were synthesized using the chemical co-precipitation method with a view of developing flexible and easily processable ferromagnetic materials with high mouldability to be used as microwave absorbers. The nanoparticles prepared were incorporated into natural rubber through latex stage processing. This novel processing method gives better dispersion of particles in the rubber matrix. The composites were characterized using XRD, SEM, vibrating sample magnetometer, dynamic mechanical analyzer, cavity perturbation, thermogravimetry (TGA), and Fourier transform infrared photoacoustic spectroscopy (FTIR-PAS). A notable improvement in the mechanical properties of composites was observed upon adding Fe3O4 particles. Magnetic and microwave characteristics of the composites indicate the formation of a flexible ferromagnetic material with good microwave absorption characteristics. (C) 2015 Published by Elsevier B.V.
Keywords: Fe3O4; Ferromagnetic; FTIR-PAS; Microwave absorption; Natural rubber; SEM; XRD